2013
DOI: 10.1021/np4003977
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Engineered Sulfated Glucans from Rice Bran Exert Strong Antiviral Activity at the Stage of Viral Entry

Abstract: Attachment and entry of many viruses are mediated by their affinity for polysaccharides present on the surface of target cells. In this paper, we demonstrate that sulfated glucans isolated from rice (Oryza sativa) can be utilized as experimental drugs exerting strong antiviral activity. In particular, oleum-DMF-based extraction is described as a procedure for the generation of chemically engineered glucans from commercially available rice bran. The one-step procedure has the potential to provide a spectrum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…As PDGFRα provides an additional CMV entry pathway into trophoblasts, specific inhibitor(s) of this pathway, in combination with potent neutralising antibodies against viral pentameric complex and gB may provide a more effective prevention of CMV infection in placental trophoblast cells, and possibly other placental cell types. In a further study, chemically engineered sulfated glucans were also shown to have high antiviral activity against CMV at the stage of viral entry into human fibroblasts 77 , and may be promising candidates for drug development and antiviral strategies.…”
Section: Discussionmentioning
confidence: 91%
“…As PDGFRα provides an additional CMV entry pathway into trophoblasts, specific inhibitor(s) of this pathway, in combination with potent neutralising antibodies against viral pentameric complex and gB may provide a more effective prevention of CMV infection in placental trophoblast cells, and possibly other placental cell types. In a further study, chemically engineered sulfated glucans were also shown to have high antiviral activity against CMV at the stage of viral entry into human fibroblasts 77 , and may be promising candidates for drug development and antiviral strategies.…”
Section: Discussionmentioning
confidence: 91%
“…Given the RB-mediated protection against bacterial pathogens (7)(8)(9) and the stimulatory effects on both the innate and adaptive immune systems, RB represents a promising natural food product for modulating mucosal immunity and protecting against diarrhea from major enteric pathogens such as human rotavirus. The gnotobiotic (Gn) pig model of human rotavirus (HRV) infection and diarrhea has been extensively utilized to study HRV infection and vaccination (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…For example, Wang et al. () modified the water‐soluble polysaccharide RBPSs2a, which was purified from RB, with sulfates to obtain SRBPSs2a, and the anti‐tumor activity of the polysaccharide was higher after modification (Ray et al., ). One of the most widely studied modified polysaccharides, MGN‐3, which is mainly composed of arabinoxylan from RB, was modified using carbohydrate‐hydrolyzing enzymes extracted from shiitake mushrooms (Ghoneum, ; Pérezmartínez et al., ).…”
Section: Introductionmentioning
confidence: 99%